Heterogeneous primaries in CR4BP - A. Ansari, Abdullah; Ali, Ashraf; Shalini, Kumari; Alam, Mehtab (International Journal of Advanced Astronomy, 2019)
This paper investigates the motion of the massless body moving under the influence of the gravitational forces of the three equal heterogeneous oblate spheroids placed at Lagrangian configuration. After determining the equations of motion and the Jacobian constant of the massless body, we have illustrated the numerical work (Stationary points, zero-velocity curves, regions of motion, Poincare surfaces of section and basins of attraction). And then we have checked the linear stability of the stationary points and found that all the stationary points are unstable.Â